2017
DOI: 10.1002/cam4.1013
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of crosstalk between tumor and tumor microenvironment by β‐D mannuronic acid (M2000) in murine breast cancer model

Abstract: Metastasis is the main cause of death in breast cancer patients. Inflammatory processes following crosstalk between tumor cells and tumor microenvironment play an important role in progression and metastasis of cancer. Hence, targeting of these interactions may represent a novel promising strategy for breast cancer therapy. So, we investigated the effects of β‐D mannuronic acid (BDM), a new antiinflammatory agent, on 4T1 breast cancer cell line both in vitro and in vivo. Proliferation assays revealed low‐cytot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 50 publications
(58 reference statements)
1
24
0
Order By: Relevance
“…Therefore, M2000 is suggested to have therapeutic efficacy in RA via anti‐angiogenic mechanisms. Also, based on our previous study demonstrating the efficacy of M2000 in decreasing tumor growth and metastasis in murine breast cancer model, and regarding the central role of angiogenesis in the metastasis process, it is suggested that, in addition to preventing chronic inflammation, part of the efficacy of M2000 in that study is attributable to its anti‐angiogenic effects . The current study, together with our previous studies on M2000, clearly demonstrates the role of this molecule in modulating three distinct but related processes including inflammation, angiogenesis, and metastasis.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Therefore, M2000 is suggested to have therapeutic efficacy in RA via anti‐angiogenic mechanisms. Also, based on our previous study demonstrating the efficacy of M2000 in decreasing tumor growth and metastasis in murine breast cancer model, and regarding the central role of angiogenesis in the metastasis process, it is suggested that, in addition to preventing chronic inflammation, part of the efficacy of M2000 in that study is attributable to its anti‐angiogenic effects . The current study, together with our previous studies on M2000, clearly demonstrates the role of this molecule in modulating three distinct but related processes including inflammation, angiogenesis, and metastasis.…”
Section: Discussionsupporting
confidence: 71%
“…In an investigation, our findings showed that M2000 is able to decrease the activities of MMP‐2, MMP‐9 in 4T1 breast cancer cell line. Moreover, the in vivo results showed that M2000 strongly inhibits tumor growth and increases lifespan as compared with control mice . In another study, our results showed that M2000 is able to decrease the gene expression and gelatinolytic activities of MMP‐2 and MMP‐9 in PMA‐differentiated THP‐1 cell line likely through inhibiting CD147 .…”
Section: Discussionmentioning
confidence: 52%
“…β-D mannuronic acid (BDM) is a MMP inhibitor, inhibiting MMP-2 and MMP-9 involved in invasion, metastasis, and angiogenesis 38 . BDM possesses anti-metastatic activity and inhibits tumor growth by suppressing inflammatory chemokine and tumor–promoting cytokines 39 . MMP-14 located on the cell surface, is a potential target to stop metastasis and a novel antibody-mediated MMP-14 blockade seems to limit hypoxia and metastasis in triple negative breast cancer (TNBC) models 40 .…”
Section: Introductionmentioning
confidence: 99%
“…In the study of BC murine model and 4T1 cell line by Mirshafiey and co‐workers, it has been shown that M2000 significantly decreases MMP‐2, MMP‐9 activities and adhesion of 4T1 cells to collagen I, fibronectin and laminin (major components of ECM) in a dose dependent manner . The M2000 strongly inhibits the tumour growth and increases lifespan in mice and decreases tumour mass size, which is associated with decrease in recruitment of inflammatory cells to tumour microenvironment and prevents tumour metastasis …”
Section: Discussionmentioning
confidence: 99%
“…In addition, M2000 is a reducer of C‐C Motif chemokine Ligand 22 (CCL22), transforming growth factor beta (TGFβ), Tregs and MDSCs. The aforementioned items play an important role in the progression of cancer . Based on these findings, the present study was designed to evaluate the efficacy of M2000 in the early stage of pre‐surgical BC patients under a randomize phase II clinical trial.…”
Section: Introductionmentioning
confidence: 99%